Five-year comparison of clinical and echocardiographic outcomes of pure aortic stenosis with pure aortic regurgitation or mixed aortic valve disease in the COMMENCE trialCentral MessagePerspective - Vinod H. Thourani, MD; John D. Puskas, MD; Bartley Griffith, MD; Lars G. Svensson, MD, PhD; Philippe Pibarot, DVM, PhD; Michael A. Borger, MD, PhD; David Heimansohn, MD; Thomas Beaver, MD, MPH; Eugene H. Blackstone, MD; Anna Liza M. Antonio, DrPH; Joseph E. Bavaria, MD, MPH (JTCVS Open)
Objective: To compare outcomes of aortic valve replacement (AVR) in patients with pure aortic stenosis (Pure AS) and those with pure aortic regurgitation (Pure AR) or mixed AS and AR (MAVD) in the COMMENCE trial. Methods: Of 689 patients who underwent AVR in the COMMENCE trial, patients with moderate or severe AR with or without AS (Pure AR + MAVD; n = 135) or Pure AS (n = 323) were included. Inverse probability of treatment weighting Kaplan-Meier survival curves were used for time-to-event endpoints, and longitudinal changes in hemodynamics were evaluated using mixed-effects models. Echocardiographic outcomes were assessed by an echo core laboratory and clinical outcomes adjudicated by a clinical events committee. The mean duration of follow-up was 5.3 ± 2.2 years. Results: At 5 years, adjusted safety endpoints were not statistically different between groups; no structural valve deterioration (SVD) event occurred in either group. After adjustment, the Pure AR + MAVD group had a greater change in body surface area–corrected left ventricular (LV) mass reduction (P = .03) compared to the Pure AS patients. Those patients with a baseline LV ejection fraction (LVEF) >55% continued to demonstrate preserved contractility compared to patients with an LVEF ≤55% at baseline (P < .0001). No significant difference in mean gradient (P = .07) or effective orifice area (P = .96) at 5 years was evident between the groups. Conclusions: Patients with Pure AR + MAVD demonstrated similar clinical safety and freedom from SVD at 5 years compared to those with Pure AS. There was a significant difference in LV reverse remodeling in the Pure AR + MAVD group compared to the Pure AS group at 5 years. These favorable outcomes in patients with AR may reinforce the need for treatment before irreversible changes occur.